Currency Composition and Foreign Exchange Reserves. (IMF Working Papers; Working Paper, 1988)
This study examines the determinants of the currency composition of foreign exchange reserves for both industrial and developing countries. During the period from 1976-85, our empirical results indicate that the currency composition of reserves has been influenced by each country's exchange rate arrangements, its trade flows with reserve currency countries, and the currency of denomination of its debt-service payments. The evidence is consistent with the view that managing the currency composition of a country's net foreign asset position is done more cheaply by altering the currency of denomination of assets and liabilities that are not held as reserve assets.